Pengaruh air kelapa hijau terhadap dismenorea pada remaja - Yuniza Yuniza; Marwan Riki Ginanjar (STIKes Surya Global Yogyakarta, 2022)
Dysmenorrhea is pain in the lower abdomen during the menstrual cycle. Pain usually comes before menstruation, during menstruation, until the end of the menstrual cycle. The pain that is felt makes women unable to move. One of the effect of dysmenorrhea is decrease concentration, there is no motivation to go to college, cannot present optimally. The management of dysmenorrhea is done non-pharmacologically by consuming green coconut water. The aim of this research is to determine the effect of green coconut water on dysmenorrhea in adolescents in the Muhammadiyah Palembang IKesT Dormitory. Research Methods: This research was a pre-experimental study using a two group pretest posttest design with a quantitative approach. The instrument used the Numeric Rating Scale (NRS). The sampling technique was purposive sampling on students of the Muhammadiyah Palembang IKesT Dormitory with a total sample of 26 intervention groups and 26 control groups. Data processing using independent and dependent t test. The result of the intervention group were the pain scale before giving green coconut water was 5.62 and after 1 with a p value of 0.006. The pain scale before being given was 5.38 and after 3.78 with a p value of 0.001. Conclusion: There was a difference in pain in the control and intervention groups after being given green coconut water